Effect of vapor pressure deficit on growth and yield of pearl millet germplasm originating from semi-arid, semi-humid and humid regions - Garba, Hadizatou; Hamidou, Falalou; Abdou, Harou; Burridge, James; Vadez, Vincent (Frontiers in Plant Science, 2024)
The increase in vapor pressure deficit (VPD) is among the expected changes in future climate and understanding its effect on crops growth is of much significance for breeding programs.Three groups (G1, G2, G3) of pearl millet germplasm, originating from regions with different rainfall intensities, were grown in the field during periods of high and low VPD. The groups G1, G2, and G3 were respectively from Guinean (rainfall above 1000 mm), Soudanian (rainfall between 600-900 mm) and Sahelian zones (rainfall between 600-300 mm) of Africa.The objective was to assess if there was any growth response difference among the germplasm groups. Four trials were conducted, two in the dry season of 2019 (Ds19) and 2020 (Ds20) with average VPD 3.62 and 2.92 kPa respectively, and two in the rainy season of 2019 (Rs19) and 2020 (Rs20) with average VPD 1.14 and 0.61 kPa respectively. In order to avoid possible confounding effects of radiation on millet growth and yield, data were normalized by the quantity of light received during each season. After this normalization leaf area and grain yield decreased in highest VPD seasons while tiller number decreased only in Ds19 (one high VPD season). The comparison of the 3 germplasm groups indicates that G3 the germplasm group from Sahelian regions showed greater tolerance to high VPD than G1 and G2. Germplasm from the G3 group could be a good material for developing tolerant germplasm to future climates that is bound to have high VPD.